PENGARUH PERADABAN ISLAM DI PAPUA - M. Irfan Mahmud (BALAI ARKEOLOGI PAPUA, 2012)
Research on Islamic civilization in Papua has been implemented since 1996. Starting with limited exploration in the area of Raja Ampat Sorong regency. Then proceed in Fak-Fak regency and Kaimana. Study conducted found that the influence of Islamic civilization was stimulated by trade dynamics, especially the Islamic empire in the Moluccas, the Kingdom of Ternate and Tidore. In its development, the kingdom of Tidore absolute power and give a big hand in the formation of Islamic civilization color via satellite countries in the Bird’s Head region along the surrounding islands to colonial entered. Many archaeological remains indication, other than oral sources and the tradition continues. Archaeological remains were found, including the mosques, tombs, pottery, ceramics, religious symbols, and ancient manuscripts. This paper will focus the discussion on three things: (1) a review of Islamic civilization studies conducted Jayapura Archeology, particularly the constraints and problems that still contain the debate to date, (2) the elements of Islamic civilization are essential, such as cultural character and government (petuanan), network scholars, and elements of material culture, and tradition, (3) Islamic cultural traditions inherited colored Muslim communities in certain pockets on the coast. Thirdly it is expected to provide information and research results that will be developed within the framework of the Islamic era in Papua theme.